The Effects of Using Chemicals to Remove Slime from African Giant Land Snails Flesh during Processing on Some Nutritional and Biochemical Parameters - Agbor Esther Etengeneng; Lamye Glory Moh; Suffo Kamela Arnaud Landry (International Journal of Food Science)
The effects of chemicals commonly used in Cameroon to eliminate slime from the flesh of the African giant land snail, Archachatina marginata, during processing on some nutritional and biochemical parameters were investigated. Groups of snails were processed with these chemicals at three different concentrations. Proximate analysis of all the treated snail groups was carried out, and groups with the highest concentration of each chemical were used to compose diets for experimental rats. Thirty weanling male Wistar albino rats (31.25±3.09 g) aged 21days old were distributed into four groups and fed with 10% protein based diets of A. marginata named D1 (washed with only water), D2 (lime C-treated), D3 (alum C-treated), and D4 (salt C-treated). The crude protein contents of the treated groups reduced significantly when compared with the control (CW), with lime C-treated (LC) having the least here and in crude fiber, but higher (LC, LB, and LA) in dry matter. There was a significant reduction in the crude lipid of alum C-treated (AC) and salt A-treated (SA). In vivo studies showed a general decrease in food consumption, weight gained, efficiency of feed utilization (EFU), true protein digestibility (TD) (except D2), and hematological indices (RBCs (red blood cells), PCV (packed cell volume) of the treated groups (D2, D3, D4) when compared to the control (D1). On the other hand, an increase in the relative weight of the liver (RWL), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and total cholesterol was observed with some of the treated diets; meanwhile, protein efficiency ratio (PER), net protein ratio (NPR), relative weight of the kidneys (RWK), HDL cholesterol, and triglycerides were not affected by these diets. These chemicals should only be used at low concentrations or not at all because of its toxicity at high concentrations.